2015
DOI: 10.4028/www.scientific.net/amm.787.485
|View full text |Cite
|
Sign up to set email alerts
|

Zone Wise Properties of Friction Stir Welded Copper – Stainless Steel Joints Using Digital Image Correlation

Abstract: Recent developments in imaging non destructive evaluation techniques offer possibilities of quantitative measurement of strain localizations associated with plastic instabilities. Digital image correlation is a technique now being widely employed for studying the temporal strain evolution associated during tensile deformation. This work focuses on the application of digital image correlation to visualise the two dimensional strain evolutions in the weld zone, heat affected zone and the base metal during monoto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 6 publications
1
10
0
Order By: Relevance
“…Despite of this, it is reported that, Cu-SS can be joined with the help of different techniques such as shielded metal arc welding (SMAW), Tungsten/metal gas suspended arc welding, brazing, laser beam welding (LBW), electron-beam welding (EBW), hot isostatic pressing (HIP), explosive welding (EW), friction stir welding (FSW), etc. [10][11][12][13][14][15][16][17][18][19][20][21][22][23]. The melting of the material causes various problems of solidification cracking, porosity, and residual stresses that triggering premature failure [10][11][12][13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Despite of this, it is reported that, Cu-SS can be joined with the help of different techniques such as shielded metal arc welding (SMAW), Tungsten/metal gas suspended arc welding, brazing, laser beam welding (LBW), electron-beam welding (EBW), hot isostatic pressing (HIP), explosive welding (EW), friction stir welding (FSW), etc. [10][11][12][13][14][15][16][17][18][19][20][21][22][23]. The melting of the material causes various problems of solidification cracking, porosity, and residual stresses that triggering premature failure [10][11][12][13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12][13][14][15][16][17][18][19][20][21][22][23]. The melting of the material causes various problems of solidification cracking, porosity, and residual stresses that triggering premature failure [10][11][12][13][14][15][16][17][18][19]. Furthermore, LBW and EBW necessitate close control over the parameters which results in a higher degree of complexity [10][11][12][13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations